Quagmire Tiarello couldn't be better - Larsen, Mylisa (Clarion Books, an imprint of HarperCollins Publishers, 2024)
Quagmire Tiarello prides himself on not needing anything from anybody. Sure, his mom is skipping work again and showing signs of going into one of her full-out spins, but it's nothing he can't handle. He's used to her up-and-down moods, even if this time it feels a little different. Then his mom disappears, and Quag must find shelter with an uncle he didn't know he had. Should he come clean about his mother's mental health challenges? Or can he use his carefully honed skills to bluff long enough to find his mom and get home? Readers will root for Quag as he finds himself rethinking his world and learning to accept help from the people who love him.